Enhancing Sharia Kur Effectiveness In Batang: Regulatory Barriers And Msme Economic Growth - Ubaidillah, Muhammad; Aurelia, Karina; Sholih, Muhammad Wildan (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a vital driver of Indonesia’s economy, particularly in Batang Regency, which is known for its thriving agricultural, craft, and culinary sectors. This study evaluates the effectiveness of the sharia-based Kredit Usaha Rakyat (KUR) disbursement at Bank Syariah Indonesia (BSI) KCP Batang, with a focus on regulatory barriers and economic impacts. Employing qualitative methods—including interviews, observations, and document analysis—the research identifies a structured process comprising application, verification, field surveys, feasibility analysis, contract signing, and fund disbursement. However, approximately 20% of applications experience delays due to incomplete business permits and extended survey times in rural areas, further exacerbated by the low financial literacy of MSME actors. While KUR has successfully increased working capital and even boosted revenue by up to 30% for some beneficiaries, the lack of post-disbursement support limits its long-term impact. Based on the findings, this study offers data-driven recommendations: the implementation of digital verification systems, the provision of financial literacy workshops, and collaboration with local governments to streamline permit issuance. These strategies align with national MSME financing objectives set by the Coordinating Ministry for Economic Affairs.